Chinese Stroke Association guidelines for clinical management of cerebrovascular disorders: executive summary and 2019 update of clinical management of intracerebral haemorrhage. Issue 4 (1st December 2020) - Cao, Yong; Yu, Songlin; Zhang, Qian; Yu, Tao; Liu, Yanfang; Sun, Zhenghui; Zhao, Meng; Wang, Wen; Zhao, Ji Zong
Abstract : Aim: This evidence-based guideline aims to present current and comprehensive recommendations for the diagnosis and management of spontaneous intracerebral haemorrhage (ICH). Methods: A formal literature search was conducted on MEDLINE (1 January 1990 to 30 June 2019). Data were synthesised using evidence tables. The members of the working group met by teleconference to update and formulate data-based recommendations. The recommendations are graded according to levels of evidence grading algorithm of the Chinese Stroke Association. The guideline draft has been reviewed by Chinese Stroke Association Stroke Council Guideline Writing Committee. Results: Evidence-based guideline is proposed for the management of patients with ICH. The focus of the guideline is divided into the diagnosis and aetiology of ICH, management of ICH in emergency department, surgical treatment for removal of hematoma, management of complications and prevention of secondary ICH. Conclusions: This guideline provides a framework for ICH management. Early active and reasonable treatment may improve the clinical outcome of patients.